ANALISIS PELAYANAN PRIMA (EXCELLENT SERVICE) PADA NASABAH DI BANK JATIM CABANG SAMPANG - Putri, Vera Eka Diana; Meirinawati, Meirinawati (Publika, 2023)
The government strives to provide the best public services to provide comfort to the community through regulations. However, in the field there are still service facilitators who do not meet excellent service, including services in the banking sector. One example of excellent service analysis for customers at Bank Jatim Sampang Branch. This study aims to describe the analysis of excellent service for customers at Bank Jatim Sampang Branch. This study aims to describe the analysis of excellent service for customers at Bank Jatim Sampang Branch. The type of research used is qualitative descriptive. The focus of his research uses the A6 theory according to Barata (2014), namely attitude, attention, action, ability, appearance and accountability. Data collection techniques are carried out through observation, interviews, literature studies and documentation. Data analysis is carried out data collection, data reduction, data presentation and conclusions. The results showed that the attitude of Bank Jatim Sampang Branch in implementing an impatient attitude to serve customers. Attention, Bank Jatim Sampang Branch in giving equal attention is not conveyed well to customers. Action, Bank Jatim Sampang Branch in its services has fulfilled the principles of fast, precise, economical, and safe. The ability of Bank Jatim Sampang Branch has employees with accumulated abilities. Appearance, Bank Jatim Sampang Branch applies and meets the criteria for good appearance in terms of physical and non-physical. Accountability, Bank Jatim Sampang Branch is well responsible even though it still needs improvement. The advice in this study, in providing services must be patient without any difference in treatment of customers during the process of providing excellent service at Bank Jatim Sampang Branch. Keywords : Public Service, Excellent Service, Banking Service